2021
DOI: 10.5194/essd-13-3115-2021
|View full text |Cite
|
Sign up to set email alerts
|

Southern Ocean cloud and aerosol data: a compilation of measurements from the 2018 Southern Ocean Ross Sea Marine Ecosystems and Environment voyage

Abstract: Abstract. Due to its remote location and extreme weather conditions, atmospheric in situ measurements are rare in the Southern Ocean. As a result, aerosol–cloud interactions in this region are poorly understood and remain a major source of uncertainty in climate models. This, in turn, contributes substantially to persistent biases in climate model simulations such as the well-known positive shortwave radiation bias at the surface, as well as biases in numerical weather prediction models and reanalyses. It has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 103 publications
3
21
0
Order By: Relevance
“…Vignon et al (2021) showed that immersion freezing INP measurements collected with filters exposed for 24-48 hr from a ship platform located near the Mawson Antarctic coastal station suggest a log-linear extrapolation with a different slope in the temperature regime of interest here, resulting in 10 −5 L −1 as an upper bound for INP concentrations within the rime-splintering temperature zone. Spectra of INP from filters exposed for 24 hr aboard the RV Tangaroa at 50-80°S, which had limits of detection near −15°C (Kremser et al, 2021), suggest an INP concentration of 10 −5 L −1 at −13°C, matching the concentrations predicted in the extrapolation in Figure 4. Regardless, all these estimates suggest that the observed ice should have very low number concentrations if primary nucleation alone is active.…”
Section: Analysis Of Primary Ice Nucleation and Rime Splinteringsupporting
confidence: 68%
“…Vignon et al (2021) showed that immersion freezing INP measurements collected with filters exposed for 24-48 hr from a ship platform located near the Mawson Antarctic coastal station suggest a log-linear extrapolation with a different slope in the temperature regime of interest here, resulting in 10 −5 L −1 as an upper bound for INP concentrations within the rime-splintering temperature zone. Spectra of INP from filters exposed for 24 hr aboard the RV Tangaroa at 50-80°S, which had limits of detection near −15°C (Kremser et al, 2021), suggest an INP concentration of 10 −5 L −1 at −13°C, matching the concentrations predicted in the extrapolation in Figure 4. Regardless, all these estimates suggest that the observed ice should have very low number concentrations if primary nucleation alone is active.…”
Section: Analysis Of Primary Ice Nucleation and Rime Splinteringsupporting
confidence: 68%
“…The atmospheric DMS concentration [𝐷𝑀𝑆] 𝑎𝑡𝑚 was neglected as this is several orders of magnitude lower than the dissolved DMS concentration (Kremser et al, 2021). Flux estimates were obtained using DMS concentrations from three different depths: FSML corresponds to DMS air-sea flux calculated using DMS concentration in the SML, FSSW to DMS concentration in the SSW, and F5 m to DMS concentration at 5 m depth from the CTD.…”
Section: Dms Air-sea Flux Calculationmentioning
confidence: 99%
“…via 40 m of conductive hose. Within the laboratory, a passive cavity aerosol spectrometer probe (PCASP-100X; Droplet Measurement Technologies) and a differential mobility particle sizer (DMPS, TSI) mea-sured the ambient concentration of particles suspended in the atmosphere (Kremser et al, 2020). The PCASP measured the number concentration size spectra of particles suspended in the boundary layer in 30 size bins (0.1-3.0 µm) every minute.…”
Section: Measurementsmentioning
confidence: 99%
“…When data from the DMPS were not available, measurements from the PCASP were used to constrain the abundance and size of accumulation mode particles. Further details on sampling set-up and analysis, including correction factors for losses through the sampling line and methods for handling contamination from ship exhaust, are described in Hartery et al (2020) and Kremser et al (2020). In parallel to the size-resolved particle concentration spectra generated by the SMPS and PCASP, the total number of cloud condensation nuclei (CCN) was measured using a CCN counter (CCNC-100; Droplet Measurement Technologies).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation